A new species of the flat bug genus Aneurus from Japan (Hemiptera: Heteroptera: Aradidae) - Shimamoto, Shusuke; Ishikawa, Tadashi (Zootaxa, 2022)
A new aneurine flat bug species, Aneurus (Aneurodes) taterasanus sp. nov. (Hemiptera: Heteroptera: Aradidae), is described from western and southwestern Japan, as the fifth species of the subgenus Aneurodes Heiss, 1998, and the first record of the subgenus from the country. The structure of the phallus of this new species with the endosoma everted and inflated is documented in detail for the first time in the subfamily Aneurinae. A key to species of the subgenus Aneurodes and another one to species of the genera Aneurus Curtis, 1825 and Paraneurus Jacobs, 1986 occurring in Japan are provided.